Analisis Peran Lembaga Keuangan Mikro Syariah dalam Mendukung Integrasi Pemasaran Berbasis E-Commerce untuk Meningkatkan Daya Saing UMKM - Nur Hasanah; Yuni Harlina; Syahra Saroja Utami; Khairunnisa Khairunnisa; Abdur Rahman Muhammad (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the role of Islamic Microfinance Institutions (LKMS) in supporting e-commerce-based marketing integration to improve the competitiveness of MSMEs in the digital era. The method used is library research with a descriptive qualitative approach. Data were obtained from various literature sources such as scientific journals, books, articles, research reports, and relevant academic documents. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results show that LKMS plays a significant role in providing access to financing, expanding financial inclusion, and providing business assistance for MSMEs. Meanwhile, e-commerce is able to expand markets, increase promotional effectiveness, and strengthen business competitiveness through the use of digital technology. The integration of LKMS and e-commerce creates a synergy that supports the digital transformation of MSMEs through financing, increasing digital literacy, and expanding market access. Collaboration between various parties is needed to realize optimal and sustainable MSME development.